Prevalence of colorectal malignant and pre-malignant diseases in faecal immunochemical test positive individuals: an observational study - Siddiquee, Muhammad Ali; Islam, M. Shahidul; Ovi, Mir Rasekh Alam; Jalal, Muhammed Tanvir; Uddin, Mohammad Azim; Saha, Kalyan Kumar; Nasrin, Shamima; Ali, M. Sumon; Akter, Joynab (International Surgery Journal, 2025)
Background: Colorectal cancer (CRC) is a challenging clinical entity worldwide. Adenomatous polyps are considered precursors to cancer. For early detection of polyps or ulcers, different screening investigations like colonoscopy, faecal immunochemical test (FIT), gFOBT, CT colonography etc. are used. Despite colonoscopy is being a highly accurate and gold standard therapeutic, it is not easily available in remote areas. The FIT, one of several tests available for CRC screening, is currently used in many countries and well accepted to all patients. Methods: To find out the prevalence of colorectal malignant and pre-malignant diseases in FIT positive individuals. This prospective cross-sectional observational study was done in the department of colorectal surgery, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka. A total 140 patients were selected according to the inclusion and exclusion criteria. FIT was done who matched. Colonoscopy was done in the FIT positive individuals. Results: The study patients were aged ≥45 years, with a mean age of 51.73±7.97 years. The most common clinical finding was abdominal pain (n=117), followed mucous discharge (n=56) and changes in bowel habit (n=47). Colonoscopy revealed that 50% of the patients had polyps, 10.71% had nonspecific ulcers, 2.86% had growths, and 12.14% had haemorrhoids. Histopathology showed that 61.43% of the polyps were hyperplastic polyps, and 63.16% of the ulcers were non-specific colitis. Most of the patients had single polyps in colonoscopy. Sensitivity, specificity and PPV of FIT is 85.7%, 97.5% and 66.4% respectively. Conclusions: The consistent evidence linking FIT positivity to the presence of colorectal malignant and pre-malignant diseases reinforces its efficacy as a frontline screening tool.